2007
DOI: 10.1097/aud.0b013e31803150de
|View full text |Cite
|
Sign up to set email alerts
|

Using Current Steering to Increase Spectral Resolution in CII and HiRes 90K Users

Abstract: The HiResolution Bionic Ear has the ability to steer current through simultaneous stimulation of adjacent electrode contacts. These data show that the majority of subjects perceive additional spectral channels other than those associated with stimulation of the fixed electrodes when current steering is implemented. The results suggest that the average cochlear implant user may have significantly more place-pitch capability than is exploited presently by cochlear implant systems. Current steering will be implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 3 publications
2
78
0
3
Order By: Relevance
“…Considering the psychophysical evidence that implant listeners generally do not make full use of their available channels to extract spectral information (Fishman et al, 1997;Friesen et al, 2001), prudent deactivation of channels affected by a poor electrode-neuron interface-and the subsequent remapping of frequency bands to the remaining channels-has the potential to improve the perception of speech and other spectrally complex stimuli. With the growing application of current focusing and current steering strategies (Koch et al, 2007;Mens & Berenstein, 2005;van den Honert & Kelsall, 2007), optimizing the allocation of spectral information becomes increasingly important. (For further discussion of channel reprogramming, see Here we have shown that tripolar configuration threshold is correlated with both psychophysical tuning curve width and growth of loudness.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the psychophysical evidence that implant listeners generally do not make full use of their available channels to extract spectral information (Fishman et al, 1997;Friesen et al, 2001), prudent deactivation of channels affected by a poor electrode-neuron interface-and the subsequent remapping of frequency bands to the remaining channels-has the potential to improve the perception of speech and other spectrally complex stimuli. With the growing application of current focusing and current steering strategies (Koch et al, 2007;Mens & Berenstein, 2005;van den Honert & Kelsall, 2007), optimizing the allocation of spectral information becomes increasingly important. (For further discussion of channel reprogramming, see Here we have shown that tripolar configuration threshold is correlated with both psychophysical tuning curve width and growth of loudness.…”
Section: Discussionmentioning
confidence: 99%
“…Due to broad spread of currents through the scala tympani, it is possible to use electrodes separated by a distance of as much as 16 mm to evoke such intermediate pitches . The resolution, identified as the number of intermediate pitches, achievable with simultaneous stimulation has been quantified in several studies (Donaldson et al, 2005;Firszt et al, 2007;Koch et al, 2007). Generally, it is found that on average 4-7 intermediate pitch sensations per pair of adjacent electrodes (spaced between 0.85 and 1.1 mm, depending on electrode type) could be perceived using current steering, with a trend for basal pairs to produce fewer intermediate pitches.…”
Section: Evidence Of Current Steering In Human Subjectsmentioning
confidence: 99%
“…Additionally, the system includes a short-duration current steering phase, to avoid charge-buildup, and therefore glitching at turn-on and turn-off, while reducing power consumption compared to traditional current-steering systems [22]. A study [23] recently reported that using current steering techniques can additionally be considered for increased spectral resolution. Finally, as an added precaution, once each CIS cycle, all the stimulation electrodes are grounded, such that any residual charge that may have accumulated (due to device mismatch, electrode variation, etc.)…”
Section: System Overviewmentioning
confidence: 99%